Monocytes, macrophages, and their potential niches in synovial joints: therapeutic targets in post-traumatic osteoarthritis? - Haubruck, Patrick; Pinto, Marlene Magalhaes; Moradi, Babak; Little, Christopher B.; Gentek, Rebecca (Frontiers in immunology, 2021)
Synovial joints are complex structures that enable normal locomotion. Following injury, they undergo a series of changes, including a prevalent inflammatory response. This increases the risk for development of osteoarthritis (OA), the most common joint disorder. In healthy joints, macrophages are the predominant immune cells. They regulate bone turnover, constantly scavenge debris from the joint cavity and, together with synovial fibroblasts, form a protective barrier. Macrophages thus work in concert with the non-hematopoietic stroma. In turn, the stroma provides a scaffold as well as molecular signals for macrophage survival and functional imprinting: “a macrophage niche”. These intricate cellular interactions are susceptible to perturbations like those induced by joint injury. With this review, we explore how the concepts of local tissue niches apply to synovial joints. We introduce the joint micro-anatomy and cellular players, and discuss their potential interactions in healthy joints, with an emphasis on molecular cues underlying their crosstalk and relevance to joint functionality. We then consider how these interactions are perturbed by joint injury and how they may contribute to OA pathogenesis. We conclude by discussing how understanding these changes might help identify novel therapeutic avenues with the potential of restoring joint function and reducing post-traumatic OA risk.